2015
DOI: 10.3390/toxins7104054
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Shiga Toxin 1, 2 and Their Subunits on Cytokine and Chemokine Expression by Human Macrophage-Like THP-1 Cells

Abstract: Infection by Shiga toxin (Stx)-producing enterohemorrhagic Escherichia coli (EHEC) results in severe diarrhea, hemorrhagic colitis, and, occasionally, hemolytic-uremic syndrome (HUS). HUS is associated with an increase in pro-inflammatory cytokines and chemokines, many of which are produced by macrophages in the kidneys, indicating that localized host innate immunity likely plays a role in renal pathogenesis. EHEC serotypes may express one or two classes of serologically defined but structurally and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Previous studies revealed that macrophages derived from THP-1 express Gb3 on their membrane [33,34]. As consequence, these cells are able to respond to Stx1/Stx2 [35,36], inducing cytokine/chemokine production, ribotoxic stress, and death of macrophages [22]. Thus, to further elucidate the Stx2-dependent mechanism responsible for macrophage death, we treated cultures with an anti-Stx2 neutralizing antibody since the beginning of 125/99 infection [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that macrophages derived from THP-1 express Gb3 on their membrane [33,34]. As consequence, these cells are able to respond to Stx1/Stx2 [35,36], inducing cytokine/chemokine production, ribotoxic stress, and death of macrophages [22]. Thus, to further elucidate the Stx2-dependent mechanism responsible for macrophage death, we treated cultures with an anti-Stx2 neutralizing antibody since the beginning of 125/99 infection [37].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine secretion by macrophages is one of the major inflammatory responses upon bacterial stimulus. In this regard, TNF-α and IL-1β are the earliest secreted ones with special impact on EHEC pathogenesis [22], because they significantly enhance the toxin-specific glycolipid receptor (Gb3) on the endothelium and Stx2-sensitivity [23]. Thus, we assayed IL-1β levels in the supernatants of macrophages infected with 125/99.…”
Section: Intereleukin-1 Betha (Il-1β) Secretion Upon Macrophage Infecmentioning
confidence: 99%
“…It has been suggested that VT2 induces a greater expression of signalling molecules, leading to more severe disease progression in humans. VT1 and VT2 were shown to have the same level of toxicity and that A and B subunits did not induce the expression on their own (Brandelli et al, 2015). However, in macrophage-like THP-1 cells treated with VT2, 14 of the 40 cytokines or chemokines monitored showed significantly increased levels including pro-inflammatory, immune cell proliferating, growth-promoting factors and other chemokines (Brandelli et al, 2015).…”
Section: Factors Implicated In Higher Disease Severity For Vt2mentioning
confidence: 95%
“…However, in macrophage-like THP-1 cells treated with VT2, 14 of the 40 cytokines or chemokines monitored showed significantly increased levels including pro-inflammatory, immune cell proliferating, growth-promoting factors and other chemokines (Brandelli et al, 2015). These factors have been associated with HUS suggesting that VT2 may play a greater role than VT1 in enhancing macrophage infiltration and fibrin deposition (Brandelli et al, 2015;Fu et al, 2004). Also, both TNF-ɑ and IL-1β, as well as a few other cytokines to a lesser extent, induce Gb3 expression and may contribute to greater impact of the toxin at target organs (van der Kar et al, 1992).…”
Section: Factors Implicated In Higher Disease Severity For Vt2mentioning
confidence: 96%
See 1 more Smart Citation